CdS-dots decorated WO3 nanorods photocatalyst with highly ordered interfacial structure for enhanced photocatalytic activities via Z-scheme mechanism. (19th February 2021) - Zhao, Longfei; Zhang, Yuan; Ye, Zhupeng; Chen, Xin; Zeng, Yanwei
Abstract: Constructing heterostructure is regarded as one of the most promising strategies for the enhancement of photocatalytic activities, because it can make charge carriers separated more efficiently at the interface. Herein, CdS-WO3 heterostructure photocatalysts with highly ordered and intimate interfacial structure between the two constituent phases have been successfully prepared via a heterogeneous nucleation and growth of CdS nanoparticles on the surface of WO3 nanorods, which were fulfilled through a controlled release of S 2− in the aqueous solution containing Cd 2+ by the reaction of NH3 with thioacetamide. The as-prepared photocatalysts were carefully studied in morphology and interfacial structure by FESEM and HRTEM, along with the other characterizations by XRD, XPS, and UV–visible absorption spectra. Under the irradiation of mercury lamp, the photocatalyst with 6 wt% CdS could afford a degradation rate of methyl orange (MO) of 94.6% in 70 min, 5.84 and 2.51 times as high as WO3 and CdS, through a photocatalytic degradation process mainly controlled by·O2 − as active species. In view of the distinctive alignment of energy bands of CdS-WO3, the enhanced photocatalytic activities should be attributed to the more efficient Z-scheme mechanism that allows the photogenerated holes in WO3 and electrons in CdS to function more efficiently thanks to the efficient interfacial recombination of the electrons in WO3 and holes in CdS. Graphical abstract: Image 1 Highlights: NH3 -mediated heterogeneous nucleation and growth of CdS on WO3 was realized. Highly ordered and intimate interfacial structure between CdS and WO3 was formed. Efficient Z-scheme mechanism results in an enhanced degradation rate of MO.